Regional Competitiveness and Innovation in Romania. Case Study: Evaluation of the Impact of the Regional Operational Program 2007-2013 on the Competitiveness in the North Western Region of Romania - Glazer, Vendelin Francisc (Studia Universitatis Vasile Goldiș Arad, Seria Științe Economice, 2014)
The research theme consists in identifying the impact of the European Union's development policy on the regional competitiveness in the North-Western part of Romania, as a allocation level of Regional Operational Programme funds, the impact of EU funds on the regional competitiveness, implementation of priorities within the regional development policies and determining the priority areas which are identified on the basis of the real potential and needs of a certain territory, sector or target group and regional competitiveness growth models based on structural funds.